Case Report: Add-on treatment with odevixibat in a new subtype of progressive familial intrahepatic cholestasis broadens the therapeutic horizon of genetic cholestasis - Pepe, Angela; Colucci, Angelo; Carucci, Martina; Nazzaro, Lucia; Bucci, Cristina; Ranucci, Giusy; Di Giorgio, Angelo; Vajro, Pietro; Mandato, Claudia (Frontiers in Pediatrics, 2023)
Odevixibat, an ileal bile acid transporter (IBAT) inhibitor, is effective for the treatment of pruritus in children diagnosed with progressive familial intrahepatic cholestasis (PFIC) type 1 and 2. There are no studies showing the efficacy of Odevixibat in children with different subtypes of PFIC. We describe the case of a 6-year-old girl with chronic cholestatic jaundice. In the last 12 months laboratory data showed high serum levels of bilirubin (total bilirubin x 2.5 ULN; direct bilirubin x 1.7 ULN) and bile acids (sBA x 70 ULN), elevated transaminases (x 3-4 ULN), and preserved synthetic liver function. Genetic testing showed homozygous mutation in ZFYVE19 gene, which is not included among the classic causative of PFIC and determined a new non-syndromic phenotype recently classified as PFIC9 (OMIM # 619849). Due to the persistent intensity of itching [score of 5 (very severe) at the Caregiver Global Impression of Severity (CaGIS)] and sleep disturbances not responsive to Rifampicin and Ursodeoxycholic acid (UDCA), Odevixibat treatment was started. After treatment with Odevixibat we observed: i) reduction in sBA from 458 to 71 μmol/l (absolute change from baseline: - 387 μmol/l), ii) reduction in CaGIS from 5 to 1, and iii) resolution of sleep disturbances. The BMI z-score progressively increased from -0.98 to 0.56 after 3 months of treatment (mean absolute change: 1.59). No adverse drug events (ADEs) were recorded. Treatment with IBAT inhibitor was effective and safe in our patient suggesting that Odevixibat may be potentially considered for the treatment of cholestatic pruritus also in children with rare subtypes of PFIC. Further studies on a larger scale could lead to the increasing of patients eligible for this treatment.